2009
DOI: 10.4269/ajtmh.2009.09-0252
|View full text |Cite
|
Sign up to set email alerts
|

The Microscopic Agglutination Test (MAT) Is an Unreliable Predictor of Infecting Leptospira Serovar in Thailand

Abstract: Abstract. A prospective study in Thailand identified 106 patients with culture-proven leptospirosis. The accuracy of the microscopic agglutination test (MAT) in predicting the infecting serovar was evaluated in 78/106 (74%) patients with a diagnostic titer. MAT correctly determined the infecting serovar in 26 cases (33%), indicating that this assay is a poor predictor of infecting serovar in our setting.Leptospirosis is an acute febrile illness caused by pathogenic members of the genus Leptospira . This diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 8 publications
1
65
0
2
Order By: Relevance
“…1,13,14 Studies in Barbados and Thailand emphasized that the accuracy of the MAT in predicting the infecting serovar was poor in individual cases of leptospirosis. 15,16 Paradoxical reactions and cross-reactions between serogroups may explain the difficulty to infer the identity of the infecting leptospiral serovar or serogroup. However, presumptive serogroup reactivity data could be used to gain a broad idea of the serogroups present at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…1,13,14 Studies in Barbados and Thailand emphasized that the accuracy of the MAT in predicting the infecting serovar was poor in individual cases of leptospirosis. 15,16 Paradoxical reactions and cross-reactions between serogroups may explain the difficulty to infer the identity of the infecting leptospiral serovar or serogroup. However, presumptive serogroup reactivity data could be used to gain a broad idea of the serogroups present at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that post-vaccinal titers persisted after annual (sometimes bi-annual) vaccinal injection and remain at high levels ( 1,600) because frequent exposures to field strains occur. [23][24][25] One "non-vaccinated" dog showed seropositivity at titer 800 to serogroup Icterohaemorrhagiae. This dog was an adopted adult, thus, we suggest that this animal may have previously been vaccinated.…”
Section: Animals As Reservoirs Of Leptospirosis In Mayottementioning
confidence: 99%
“…Based on the results reported for Colombia and considering: 1) that more than 80% of the studies on the prevalence of the disease were based on the MAT, 2) the difficulties of interpreting the MAT and low titers, and 3) the doubtful results on the efficacy of diagnostic tests, including the MAT [11][12][13][14][15], it can be concluded that the real prevalence of the disease in the country is still unknown and that there is a need to continue to search for methods that can accurately assess its prevalence. Work at molecular level is revealing interesting results in various parts of the world and should be considered in future works [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Other methods include: dark field examination, immunofluorescence, culture, Elisa IgM, dot Elisa, and polymerase chain reaction (PCR). The literature on these methods is extensive, and several authors have discussed the advantages and limitations of each method, as well as the discrepancies between the diagnostic results [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%